Kouros Info : het infobulletin van Gay Sportclub Kouros Eindhoven. (Eindhoven : Gay Sportclub Kouros.)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie : PB 264, 5600 AG Eindhoven
Nederlands
Periodiek